Review: Early Detection of Mycoplasma hyopneumoniae in Pigs Using Tracheo-bronchial Swab Sampling under Field Conditions - F. Vangroenweghe (Research Aspects in Agriculture and Veterinary Science Vol. 4, 2021)
Tracheo-bronchial swab (TBS) sampling is a rapid, reliable and animal-friendly diagnostic sampling of the respiratory tract for detection of Mycoplasma hyopneumoniae (M. hyopneumoniae). This review gives a broad overview of different diagnostic approaches for M. hyopneumoniae ranging from clinical signs, necropsy, microscopy to detection of the pathogen by immunohistochemistry, culture and PCR techniques. Subsequently, development, validation and obtained results are described using TBS for the early detection of M. hyopneumoniae in pigs with clinical symptoms of respiratory distress from 2 weeks of age onwards. Besides early detection related to age category, the TBS technique is also able to detect an outbreak of clinical disease due to M. hyopneumoniae in an early stage. Future perspectives on the application of TBS in diagnostic concepts, epidemiology and gilt adaptions protocols are also discussed.